2004
DOI: 10.1111/j.1365-2249.2003.02381.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD4 monoclonal antibody treatment in acute and early chronic antigen-induced arthritis: influence on T helper cell activation

Abstract: SUMMARYTo examine the effects of anti-CD4 mAb treatment in acute and chronic antigen-induced arthritis (AIA), C57BL/6 mice were treated intraperitoneally either with the depleting anti-CD4 mAb GK1·5 or with rat-IgG (control) on Days -1, 0, 1, 3, 5, and 7. Arthritis was monitored by assessment of joint swelling and histological evaluation in the acute (Day 3) and the chronic phase (Day 21) of AIA. To determine the effects on cellular immune responses, in vivo T-cell reactivity (delayed type hypersensitivity; DT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 33 publications
6
38
0
Order By: Relevance
“…Our results are in agreement with previous studies that have shown that the development of Th1-mediated experimental arthritis is critically linked with the balance of cytokines produced by Th1/ Th2 cells (45)(46)(47). Th1 responses appear most predominant at the time of arthritis onset and progressively decline during disease progression and subsequent remission, which in turn correlates with increased IL-10 levels.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in agreement with previous studies that have shown that the development of Th1-mediated experimental arthritis is critically linked with the balance of cytokines produced by Th1/ Th2 cells (45)(46)(47). Th1 responses appear most predominant at the time of arthritis onset and progressively decline during disease progression and subsequent remission, which in turn correlates with increased IL-10 levels.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, enhanced inflammatory response to Ag challenge in the IFN-␥ Ϫ/Ϫ mice is not attributed to augmented Ab production associated with complement activation, but rather to an increase of cellular effector mechanisms. Taken together, these findings clearly demonstrate that in the AIA model, which is mediated by Th cells (19,20), the absence of the characteristic Th1 cytokine IFN-␥ caused an aggravation and not a decline of inflammatory response. This response exemplifies the complexity and importance of IFN-␥ in autoimmune diseases.…”
Section: Discussionsupporting
confidence: 55%
“…The histopathological features of AIA include hyperplasia of the synovial lining; cellular infiltration of joints and periarticular tissue by neutrophils, macrophages, lymphocytes, and dendritic cells; pannus formation and destruction of cartilage and bone, all features resembling those of human RA. The similarities include also the therapeutic response to some drug treatments and the involvement of CD4 ϩ T cells in the perpetuation of arthritis (19,20). In the present study, we investigated the development of arthritis in IFN-␥-deficient (IFN-␥ Ϫ/Ϫ ) mice to determine the role of IFN-␥ in AIA.…”
Section: H Uman Rheumatoid Arthritis (Ra)mentioning
confidence: 99%
“…The mBSA-induced arthritis mouse model is a suitable and reproducible experimental system that exhibits several features with histopathological findings similar to those observed in human RA, including cartilage degradation (22). In this model, the adaptive immune response is dependent on CD4 + T cells and, to a lesser extent, is mediated by serum Ab (23). Therefore, we used this model to explore the role of NOD1 and NOD2 in the pathogenesis of experimental arthritis.…”
Section: Discussionmentioning
confidence: 99%